Ischia Group Theory 2008 - Proceedings Of The Conference In Group Theory. (World Scientific, 2009)
The volume contains a collection of research articles by leading experts in group theory, and reports of several accessible surveys of recent research in the area. The compilation provide an overview of the diversity of themes and applications that interest today's group theorists. The topics covered in this volume include: character theory, combinatorial group theory, varieties of groups, conjugacy classes, profinite groups, graphs connected with groups, subgroup structure, representation theory. Sample Chapter(s). Chapter 1: On abnormal maximal subgroups of finite groups (107 KB). Contents.